The Physics of Solids Essentials and Beyond - Economou, Eleftherios N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This textbook emphasizes a few fundamental principles and extracts from them a wealth of information. This approach also unifies an enormous and diverse subject which seems to consist of too many disjoint pieces. The book starts with the absolute minimum of formal tools, emphasizes the basic principles, and employs physical reasoning (" a little thinking and imagination" to quote R. Feynman) to obtain results. Continuous comparison with experimental data leads naturally to a gradual refinement of the concepts and to more sophisticated methods. After the initial overview with an emphasis on the physical concepts and the derivation of results by dimensional analysis, The Physics of Solids deals with the Jellium Model (JM) and the Linear Combination of Atomic Orbitals (LCAO) approaches to solids and introduces the basic concepts and information regarding metals and semiconductors. The remainder, constituting enrichment and elective material, re-examines the model under more realistic assumptions as well as new, more advanced subjects. While prerequisites include quantum mechanics, electromagnetism, and statistical physics, appendices summarizing these subjects are included to make the book more self-contained. The basic text is enhanced with worked problems, copious illustrations, chapter-end exercises and summaries. The approach, which emphasizes the underlying physical concepts, unifies to some extent a subject that can seem too diverse and consisting of too many disjoint pieces, requires from students less memorizing of facts and formalisms but more thinking.
AN OVERVIEW -- Basic Principles Summarized -- Basic Principles in Action -- A First Acquaintance with Condensed Matter -- TWO SIMPLE MODELS FOR SOLIDS -- The Jellium Model and Metals I: Equilibrium Properties -- The Jellium Model and Metals II: Response to External Perturbations -- Solids as Supergiant Molecules: LCAO -- Semiconductors and Other Tetravalent Solids -- Beyond the Jellium and the LCAO: An Outline -- MORE ABOUT PERIODICITY & ITS CONSEQUENCES -- Crystal Structure and Ionic Vibrations -- Electrons in Periodic Media. The Role of Magnetic Field -- Methods for Calculating the Band Structure -- Pseudopotentials in Action -- MATERIALS -- Simple Metals and Semiconductors Revisited -- Closed-Shell Solids -- Transition Metals and Compounds -- Artificial Periodic Structures -- DEVIATIONS FROM PERIODICITY -- Surfaces and Interfaces -- Disordered and Other Nonperiodic Solids -- Finite Systems -- CORRELATED SYSTEMS -- Magnetic Materials, I: Phenomenology -- Magnetic Materials II: Microscopic View -- Superconductivity, I: Phenomenology -- Superconductivity, II: Microscopic Theory -- APPENDICES -- Elements of Electrodynamics of Continuous Media -- Elements of Quantum Mechanics -- Elements of Thermodynamics and Statistical Mechanics -- Dielectric Function, : Formulas and Uses -- Waves in Continuous Elastic Media -- The Method LCAO Applied to Molecules -- Boltzmann$1 (Bs Equation -- Tables.s
Keywords: Physics; Engineering; Materials; Surfaces (Physics).; Physics; Condensed Matter Physics; Engineering, general; Metallic Materials; Surfaces and Interfaces, Thin Films